Experimental, DFT, molecular docking and in silico ADMET studies of cadmium-benzenetricarboxylates - Bassey, Enyi Inah; Gber, Terkumbur Emmanuel; Ekpenyong, Edison Esther; Edet, Henry Okon; Benjamin, Innocent; Ita, Imabasi Tom (Eclética Química, 2022)
The structure of the polymer [Cd(BTC)(H2O)2]n was identified by X-ray single-crystal crystallography. The complex’s stability and overall reactivity were examined at the B3LYP/6-311++G (d,p) level of theory whereas the lighter elements (H, C, and O) were studied using the LanL2DZ basis set. The electron distribution in the complex’s highest occupied molecular orbital is solely concentrated in a small area, with no electrons distributed over the cadmium. Consequently, the electrons in the complex’s lowest unoccupied molecular orbital (LUMO) were dispersed equally. The Cd atom is partially obscured by charge delocalization in the LUMO. The natural bond orbital analysis supports the result for reactivity studies. The rate of absorption, distribution, metabolism, excretion, and toxicity (ADMET) of the complex evaluated by molecular docking in a bid allowed comprehend the biological applicability. The [Cd(BTC)(H2O)2]n exhibited excellent binding affinity with proteins 1D7U and 2XCS, while by ADMET it is suggested that cytotoxicity and carcinogenicity were inactive. It is clearly shown that the complex has strong biological uses, notably for the treatment of microbial diseases.